Salivary characteristics and dental caries experience in remote Indigenous children in Australia: a cross-sectional study - Lalloo, R.; Tadakamadla, S. K.; Kroon, J.; Tut, O.; Kularatna, S.; Boase, R.; Kapellas, K.; Gilchrist, D.; Cobbledick, E.; Rogers, J.; Johnson, N. W. (BMC oral health, 2019)
Background While associations between salivary characteristics and dental caries have been well studied, we are not aware of this being assessed in a remote Indigenous child population, where lifestyles may be different from urban children. Our aim was to assess associations between caries experience and putative biomarkers in saliva, accounting for oral hygiene and dietary habits. Methods Children attending schools in an Indigenous community in remote north Queensland, Australia were invited to an oral examination by qualified and calibrated examiners. Salivary flow rate, pH, buffering capacity and loads of mutans streptococci (MS), lactobacilli (LB) and yeasts were determined. Also, data on tooth brushing frequency and soft drinks consumption were obtained via a questionnaire. Caries experience was recorded by the International Caries Detection and Assessment System (ICDAS-II), and quantified as decayed, missing and filled surfaces. Relationships between the salivary variables and the cumulative caries experience (dmfs+DMFS) in the deciduous and permanent dentitions were examined by multivariate analyses to control the effect of confounders. Results The mean cumulative decayed (DS + ds), missing (MS + ms) and filled (FS + fs) surfaces were 3.64 (SD: 4.97), 1.08 (4.38) and 0.79 (1.84) respectively. Higher salivary MS and LB counts, low tooth brushing frequency and daily soft drink consumption were significantly related to greater caries experience. Caries experience was about twice in those with ≥10^5 CFU/ml saliva counts of MS (mean = 6.33, SD: 8.40 vs 3.11, 5.77) and LB (7.03, 7.49 vs 4.41, 8.00). In the fully-adjusted multivariate model, caries experience in those with higher counts of MS and LB were 51 and 52% more than those with lower counts. Conclusions As with studies in other populations, childhood salivary counts of MS and LB were significantly associated with greater caries experience in this remote Indigenous community. To address the serious burden of oral disease, we are researching ways to promote a healthy oral environment by encouraging good dietary habits, and emphasising the importance of daily tooth brushing with a fluoridated toothpaste. Our ongoing longitudinal studies will indicate the success of measures employed to reduce the counts of bacteria closely associated with cariogenesis and their impact on caries increment. Trial registration Australian New Zealand Clinical Trials Registry ( ANZCTR ), No: ACTRN12615000693527; date of registration: 3rd July 2015.